Survey of Inmates in State and Federal Correctional Facilities, 1997 ([Verlag nicht ermittelbar], 2000)
Conducted by the Bureau of the Census, this survey provides nationally representative data on state prison inmates and sentenced federal inmates held in federally owned and operated facilities. Through personal interviews from June-October 1997, inmates in both state and federal prisons provided information about their current offense and sentence, criminal history, family background and personal characteristics, prior drug and alcohol use and treatment programs, gun possession and use, gang membership, and prison activities, programs, and services. Prior surveys of state prison inmates, called SURVEY OF INMATES OF STATE CORRECTIONAL FACILITIES, were conducted in 1974, 1979, 1986, and 1991 (see ICPSR 7811, 7856, 8711, and 6086). Sentenced federal prison inmates were first interviewed in 1991 (see SURVEY OF INMATES OF FEDERAL CORRECTIONAL FACILITIES, 1991 [ICPSR 6037]). The federal data are combined with the state data in this collection. Part 1, Numeric Data, consists of numerically-coded responses, while Part 2, Alphanumeric Data, contains free-field responses to "Specify, Other" questions in ASCII text form.